Respuesta :

Answer:

x = 3.5y

Step-by-step explanation:

Simplifying

3x + 8y + -5x + -1y = 0

Reorder the terms:

3x + -5x + 8y + -1y = 0

Combine like terms: 3x + -5x = -2x

-2x + 8y + -1y = 0

Combine like terms: 8y + -1y = 7y

-2x + 7y = 0

Solving

-2x + 7y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7y' to each side of the equation.

-2x + 7y + -7y = 0 + -7y

Combine like terms: 7y + -7y = 0

-2x + 0 = 0 + -7y

-2x = 0 + -7y

Remove the zero:

-2x = -7y

Divide each side by '-2'.

x = 3.5y

Simplifying

x = 3.5y

ACCESS MORE